1987
DOI: 10.2530/jslsm1980.8.3_89
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retinal blood flow using laser speckle phenomena

Abstract: A new method has been developed to evaluate the retinal blood flow using laser speckle phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…They used band-pass filters to facilitate the calculation of this ratio and applied the technique to measure blood flow in the skin, for example at the palm, cheek, chest and leg. Later work showed that this approach was not always applicable, and the mean frequency of the oscillations was used as the velocity indicator instead (Aizu et al 1987). The mean frequency was also used in later work on blood flow in the retina and choroid of rabbits.…”
Section: Time-varying Specklementioning
confidence: 99%
“…They used band-pass filters to facilitate the calculation of this ratio and applied the technique to measure blood flow in the skin, for example at the palm, cheek, chest and leg. Later work showed that this approach was not always applicable, and the mean frequency of the oscillations was used as the velocity indicator instead (Aizu et al 1987). The mean frequency was also used in later work on blood flow in the retina and choroid of rabbits.…”
Section: Time-varying Specklementioning
confidence: 99%
“…This approach was, then, modified and applied to an evaluation of blood flows at the ocular fundus of an albino rabbit 60 and human subjects. 61,62 Figure 5 shows the basic optical system of this type of the biospeckle flowmeter. The laser light illuminates a certain retinal area with an extended spot having a diameter of 1-3 mm, and is scattered by moving RBCs in blood vessels and capillaries and by ocular fundus tissues.…”
Section: Blood Flow Parameter In a Small Areamentioning
confidence: 99%
“…Dunn et al 6 also studied cerebral blood-flow imaging using speckles. After that, various studies on speckle blood-flow imaging have been reported including blood flow in skin tissue and retina by Fujii et al [7][8][9][10][11] , Fercher et al 12 , Briers et al 13 , and Aizu et al [14][15][16][17][18] . Other studies have been also presented on performance improvement and animal experiments [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%